1998
DOI: 10.1002/(sici)1096-9861(19980209)391:2<204::aid-cne4>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Retinoid X receptor ? gene transcripts are expressed by a subset of early generated retinal cells and eventually restricted to photoreceptors

Abstract: We have examined the distribution of the retinoid X receptor gamma (RXRgamma) in the developing chicken retina by using in situ hybridization and RNase protection assays. We detected RXRgamma transcripts as early as 4 days of embryonic development (d4) in central regions of the retina, spreading to more peripheral regions by d8. The first few RXRgamma-positive cells were scattered within the depth of the retinal neuroepithelium, but as they increased in number they became localized predominantly to the apical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 67 publications
2
23
0
Order By: Relevance
“…15 The observation that the RXRγ transcript is also present in the neural retinal cells is more surprising, since previous reports have shown that RXRγ has a very limited postnatal tissue distribution compared to other nuclear retinoid receptors. 35 RXRγ expression by cone photoreceptor cells was previously also reported by Hoover et al 36 They show the presence of RXRγ mRNA by in situ hybridization in the chick retina at two weeks post-hatching. Unfortunately, their results do not allow them to exclude rod photoreceptors from also expressing RXRγ.…”
Section: Discussionsupporting
confidence: 59%
“…15 The observation that the RXRγ transcript is also present in the neural retinal cells is more surprising, since previous reports have shown that RXRγ has a very limited postnatal tissue distribution compared to other nuclear retinoid receptors. 35 RXRγ expression by cone photoreceptor cells was previously also reported by Hoover et al 36 They show the presence of RXRγ mRNA by in situ hybridization in the chick retina at two weeks post-hatching. Unfortunately, their results do not allow them to exclude rod photoreceptors from also expressing RXRγ.…”
Section: Discussionsupporting
confidence: 59%
“…As predicted by the microarray results, a significant increase in photoreceptor markers concomitant with a decrease in retinal ganglion cell markers were observed. Thyroid hormone receptor ␤ 2 and retinoid x receptor gene ␥ are two additional genes involved in early photoreceptor development (Forrest et al, 2002;Hoover et al, 1998). Both of these genes were also observed to be upregulated in Notch1 CKO 917 RESEARCH ARTICLE Notch signaling in mouse retinal development Fig.…”
Section: Notch1 Deficient Progenitors Initiate the Photoreceptor Tranmentioning
confidence: 99%
“…However, there were fewer cells expressing visinin transcript within the EnRaxL∆C virusinfected domains. To further investigate whether EnRaxL∆C interfered with the proper development of photoreceptor cells, or just visinin marker gene expression, we examined the expression of another photoreceptor-specific gene, RXRγ (Rxrg) (Hoover et al, 1998). Rxrg exhibited a uniform pattern C.-M. A. Chen and C. L. Cepko of expression in the control, uninfected E7.5 retina (data not shown).…”
Section: Raxl Is Required For Photoreceptor Cell Developmentmentioning
confidence: 99%